Multi-stage reactive power programming using genetic algorithm - Xin Zhao; Shan Gao (2008 Third International Conference on Electric Utility Deregulation and Restructuring and Power Technologies, 2008)
Reactive power programming is a multistage multi-objectives mixed integer programming problem. In this paper, a two steps procedure is proposed to solve the reactive power programming problem. First, a genetic algorithm is adopted aimed at minimizing the cost of power loss and investment at each stage. Then a dynamic programming is adopted aimed at finding the optimal policy of the whole stages. Results are presented of applying the proposed methodology to several power systems.